Analyzing the influence of celebrities emotional and rational brand posts - Arash Ahmadi; Amirhossein Taghipour; Marc Fetscherin; Siriwan Ieamsom (My University, 2023)
Purpose The purpose of this paper is to compare two brand posts with the different content created by a celebrity (emotional content vs rational content) on Instagram and their effects on users’ willingness to use offline word of mouth (WOM) and electronic WOM (eWOM). The research model also consists of product involvement as the moderator. Design/methodology/approach Based on the results of the pretest stages, the study included two stimuli, and respondents were presented with two different brand posts (i.e. two manipulated pictures and texts on the Instagram frame). A two-group comparison (positive emotional brand post vs negative rational brand post) between-subjects experiment ( n = 214) was conducted. Findings The results indicate that WOM and eWOM are more affected by a celebrity’s emotional brand post than a celebrity’s rational brand post. Furthermore, both types of WOM are more affected through high product involvement enhanced by a celebrity’s rational brand post than through high product involvement boosted by a celebrity’s emotional brand post. Practical implications Managerial implications for social media marketing and Instagram celebrity-based branding are provided. Practical implications are also provided in the form of evidence of how the impacts of two different brand posts on positive offline WOM and eWOM are affected differently through the moderation of product involvement. Originality/value The research argues for theoretical implications for the marketing literature on celebrity endorsements. The study also tests one moderating effect on the relationship between brand post content and WOM and eWOM.
Keywords: Moderation; Digital Marketing and Social Media